Practical guide to exercise physiology the science of exercise training and performance nutrition - Murray, Bob; Kenney, W. Larry (Champaign, Illinois Human Kinetics, 2021)
Practical Guide to Exercise Physiology, Second Edition, provides students and health and fitness professionals with a simple and straightforward way to learn the principles of exercise physiology. Featuring medical artwork that puts complex systems into a digestible visual context, this text describes the fundamental science related to human physiology, metabolism, and nutrition. This book begins with a review of human physiology fundamentals, including muscles and muscle adaptation, bioenergetics, and the cardiorespiratory system. Then it applies these scientific concepts to training program design for specific fitness goals, taking into account different client populations and exercise environments. The second edition of this text features new content on relevant fitness concepts such as HIIT, periodization, and detraining. It also provides useful tools for practical application: • Fun facts and sidebars examine current topics and engage readers with additional content about the human body’s response to training. • At the end of each chapter, summary statements and review questions highlight essential information. • Performance Nutrition Spotlights offer advice and tips on using nutrition to support adaptations and improve performance. • The Index of Common Questions From Clients section collects popular inquiries from clients and points to the chapter where each of those topics is covered, helping readers to quickly access the information. Practical Guide to Exercise Physiology, Second Edition, helps readers gain confidence in the ability to explain how each exercise and movement in an exercise program will help clients achieve their goals. Ancillaries for adopting instructors are available online
Keywords: Nutrition; Exercise -- Physiological aspects